2021
DOI: 10.3390/ijms22094464
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Glioblastoma Biology, Genetics, and Current Therapies: Novel Inhibitors of the G Protein-Coupled Receptor CCR5

Abstract: The mechanisms governing therapeutic resistance of the most aggressive and lethal primary brain tumor in adults, glioblastoma, have increasingly focused on tumor stem cells. These cells, protected by the periarteriolar hypoxic GSC niche, contribute to the poor efficacy of standard of care treatment of glioblastoma. Integrated proteogenomic and metabolomic analyses of glioblastoma tissues and single cells have revealed insights into the complex heterogeneity of glioblastoma and stromal cells, comprising its tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…In gliomas, one study in U-87MG glioma cells ( 160 ) reported both GRPR and NMBR mRNA were present; however, GRP mRNA was not found, leading the authors to suggest that the GRP effect on growth of this glioma cell line was likely mediated by a paracrine mechanism. This result is somewhat surprising, both because autocrine growth, a mechanism of activation, is present in so many other tumors and also because in gliomas, autocrine mechanisms are reported for a number of other glioma growth factors, including the G-protein coupled receptor CCR5 [with its ligand CCL5 (RANTES) present in glioma cells] ( 289 ), TGFbeta1 ( 290 ), bone morphogenetic proteins (BMP4) ( 291 ), PDGF ( 292 ), and dopamine ( 293 ). In contrast, in neuroblastomas, numerous studies support an autocrine role for Bn-related peptides in BnR activation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In gliomas, one study in U-87MG glioma cells ( 160 ) reported both GRPR and NMBR mRNA were present; however, GRP mRNA was not found, leading the authors to suggest that the GRP effect on growth of this glioma cell line was likely mediated by a paracrine mechanism. This result is somewhat surprising, both because autocrine growth, a mechanism of activation, is present in so many other tumors and also because in gliomas, autocrine mechanisms are reported for a number of other glioma growth factors, including the G-protein coupled receptor CCR5 [with its ligand CCL5 (RANTES) present in glioma cells] ( 289 ), TGFbeta1 ( 290 ), bone morphogenetic proteins (BMP4) ( 291 ), PDGF ( 292 ), and dopamine ( 293 ). In contrast, in neuroblastomas, numerous studies support an autocrine role for Bn-related peptides in BnR activation.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…GB is one of the few cancers in which conventional therapies, i.e., surgery, radiotherapy, and pharmacotherapy with temozolomide (TMZ), do not increase survival of the patients [ 64 ]. As previously discussed, GB has a very heterogeneous niche, which provides therapeutic resistance and limits the availability of effective therapies.…”
Section: Possible Therapeutic Approaches Based On Cma Inhibition In P...mentioning
confidence: 99%
“…As previously discussed, GB has a very heterogeneous niche, which provides therapeutic resistance and limits the availability of effective therapies. The current chemotherapeutic for GB is usually TMZ, which is used in combination with irradiation to prevent resistance [ 64 ]. Interestingly, TMZ seems to induce expression of LAMP-2A and, therefore, CMA activity in human tumors [ 65 ], which might explain why tumor cells become resistant and PCs are, at least in part, responsible for the increased resistance [ 66 ].…”
Section: Possible Therapeutic Approaches Based On Cma Inhibition In P...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, type 1 RIPs, such as trichosanthin from Trichosanthes kirilowii [18,19] and saporin from Saponaria officinalis [20,21], display remarkable cytotoxicity against glioblastoma cell lines, which increases by linking them to specific conjugates [22]. This cytotoxicity is of interest, considering that glioblastoma is a highly aggressive brain tumor, in which malignant cells escape apoptosis by being resistant to radiotherapy and chemotherapy and unresponsive to drugs by rapidly inactivating or reducing intracellular drug concentrations or increasing the rate of DNA repair [23].…”
Section: Introductionmentioning
confidence: 99%